The Impact of Flexible Work Arrangements on Individual Performance in Government Institutions: A Systematic Review - Cipta Gusti Batara M. Nur; Henndy Ginting; Dedy Sushandoyo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid advancement of technology and the Covid-19 pandemic have accelerated the global adoption of remote work models, yet their implementation in the public sector, particularly in Indonesia, remains limited. In response, the Indonesian government introduced flexible working arrangements for civil servants to provide temporal and spatial flexibility. Nevertheless, empirical evidence on the impact of flexible work arrangement on civil servant performance is still scarce, highlighting the need for further academic investigation. The purpose of this study is to conduct a literature review on the use of flexible working arrangements on individual performance in government agencies. The method used is a systematic literature review, which will use the Scopus database in conducting a literature review. From the results of the literature review, the success of the flexible work arrangement in the government sector is influenced by the control mechanism, organizational culture, and the role of e-leadership. In addition, fragmentation between organizations without performance standards and uniform technology platforms has the potential to weaken the implementation of diversity. The implication is that the government needs to design performance standards and an integrated technology infrastructure so that the implementation of flexible work arrangements is more effective and efficient in all agencies.